Enhancing Urban Runoff Quality with Iron Slag-Modified Pervious Concrete: A Study on Mechanical Properties and Pollutant Removal Efficiency - Teymouri, Ehsan; Davis, Taylor (Civil and Sustainable Urban Engineering, 2025)
This study explores the improvement of the performance of pervious concrete (PC) for enhancing urban runoff quality by incorporating fine-grained iron slag in varying proportions, from 0% to 15% of the coarse aggregate weight. The research addresses the pressing challenges of stormwater management in urban areas, where impervious surfaces contribute significantly to increased runoff and water pollution. To tackle these issues, the study aims to optimize PC composition. Mechanical and physical properties, including compressive strength, hydraulic conductivity, and void content, were assessed. The top-performing mixes were further evaluated for their ability to improve runoff quality using a rainfall simulator and PC slabs measuring 650×450×100 mm. Initial findings showed a positive relationship between higher iron slag content and increased compressive strength, with gains of up to 13%. However, this improvement came with reduced porosity and permeability as iron slag content increased. Notably, the sample with 15% iron slag demonstrated high pollutant removal efficiencies: 42.7% for chemical oxygen demand (COD), 43.68% for total suspended solids (TSS), and 33.95% for turbidity, due to the dual effects of pore filling and contaminant adsorption by the iron slag. No significant changes were observed in NaCl and electrical conductivity (EC) levels. This study highlights the potential of optimizing iron slag content in PC to enhance its role in urban runoff management, presenting a promising approach for improving water quality in urban settings.